Correlation Between MTB/RIF Gene Xpert Cycle Threshold Values and Clinical Radiological Severity of Pulmonary Tuberculosis - Rachmi Merrina; Yanti, Budi; Yunita Arliny (Indonesian Journal of Tropical and Infectious Disease, 2024)
The determination of bacterial load was essential for assessing disease severity, transmission rate, and prognosis. Gene Xpert is a diagnostic test that provides Cycle Threshold (Ct) value as a potential measure of Mycobacterium Tuberculosis (Mtb) load. Despite its potential, there are limited reports exploring the relationship between Ct value and clinicoradiological severity. This study aimed to correlate Ct value and clinicoradiological severity of pulmonary tuberculosis (TB). The study was a retrospective design using medical record data of confirmed TB patients from January to December 2022. These patients were identified based on Gene Xpert test and classified as high, moderate, or low detection Mtb when Ct value was <16, 16-22, and 22-28, respectively. In assessing the severity of clinical using the Bandim score, thoracic TB lesions was categorized by Chest XRay into minimal, moderate, and advanced. The total of 90 TB patients and the majority were males (78.9%) aged 46-65 years (59.0%), with comorbidities (95.0%). The most of the participants had mild clinical severity (44.4%), with Ct value of 16-22 (52.2%), and moderate lesions (35.6%). The most common lesions were fibroinfiltrates on the chest X-ray (61.1%). The Ct value of <16 had a significant correlation with clinical severity of TB (p<0.05) but no significant association with advanced lesions (p>0.05). Based on the results, Ct value had a strong correlation with clinical severity in pulmonary TB. In addition, it could be used as a predictor for managing pulmonary TB patients and an important indicator for control programs.